FOSTERING THE USE OF DRAMA FOR ENGLISH LANGUAGE LEARNERS IN THE EFL CLASSROOM - Deri Sis Nanda (International Conference on Education and Language (ICEL), 2016)
Drama is a powerful tool that can engage students actively with the English learning process (Davis, 1990; Dervishaj, 2009). Drama provides a context to practice listening and speaking for learners and it makes language practice more meaningful than mechanical drills. It also gives great opportunities for them to communicate with others even when they have limited vocabulary. Therefore, the article presents the use of drama as a form of literature to encourage students to learn English as a foreign language. The method is not only to develop students’ language skills but also to provide them the real situation adopted from the real life. There will be a social engagement in doing drama activities.